Validation of a Novel Needle Holder to Train Advanced Laparoscopy Skills to Novices in a Simulator Environment. (April 2020) - Oussi, Ninos; Georgiou, Konstantinos; Larentzakis, Andreas; Thanasas, Dimitrios; Castegren, Markus; Georgiou, Evangelos; Enochsson, Lars
Background. Our aim was to determine if a newly designed Najar needle holder (NNH) shortens the time for novices to improve advanced laparoscopy (AL) techniques (suturing/knot tying), compared with a conventional macro needle holder (MNH) in a simulator. Furthermore, we aimed to validate a new video scoring system determining AL skills. Methods. Forty-six medical students performed identical surgical tasks in a prospective, crossover study evaluating AL skills (NNH vs MNH). All subjects performed a double-throw knot, 2 single-throw knots following 3 running sutures in the Simball Box (SB) simulator. After resting, subjects switched needle holders. All tasks were videotaped and analyzed using SB software and by 2 independent reviewers using the Objective Video Evaluation Scoring Table (OVEST). Trial performance expressed as SB Overall Score (SBOS) and OVEST. Results. In the group starting with NNH (followed by MNH) OVEST was consistently high during both trials (median = 12.5, range = 6.5-18.0, and median = 13.5, range = 6.5-21.0; P = .2360). However, in the group starting with MNH, OVEST improved significantly when the participants changed to NNH (median = 10.0, range = 2.5-19.5, vs median = 14.5, range = 4.5-18.0; P = .0003); an improvement was also found with SBOS (median = 37%, range = 27% to 92%, vs median = 48%, range = 34% to 70%; P = .0289). In both trials, both independent reviewers' OVEST measures correlated well: Trial 1: β = 0.97, P < .0001; and Trial 2: β = 0.95, P < .0001. A correlation also existed between SBOS and OVEST in both trials (β = 2.1, P < .0001; and β = 1.9, P = .0002). Conclusions. This study indicates a significantly higher improvement in laparoscopic suturing skills in novices training AL skills using NNH compared with MNH. Starting early, AL training in novices using NNH is a feasible option. Furthermore, OVEST used in experimental settings as an evaluation tool is comparable with the validated SBOS.